2016
DOI: 10.2147/dddt.s97221
|View full text |Cite
|
Sign up to set email alerts
|

Baicalein attenuates the quorum sensing-controlled virulence factors of Pseudomonas aeruginosa and relieves the inflammatory response in P. aeruginosa-infected macrophages by downregulating the MAPK and NFκB signal-transduction pathways

Abstract: Burgeoning antibiotic resistance and unfavorable outcomes of inflammatory injury after Pseudomonas aeruginosa infection have necessitated the development of novel agents that not only target quorum sensing (QS) but also combat inflammatory injury with the least risk of resistance. This study aimed to assess the anti-QS and anti-inflammatory activities of baicalein, a traditional herbal medicine that is widely used in the People’s Republic of China, against P. aeruginosa infection. We found that subminimum inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
67
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(73 citation statements)
references
References 58 publications
6
67
0
Order By: Relevance
“…Figure 2 ii-b) [7,56]. Overall, our findings concur with previous studies that have documented that these phytochemicals can inhibit biofilm formation [19,37]. For instance, baicalein has been reported to inhibit P. aeruginosa PA01 biofilm formation at concentrations of 32-128 µg/mL [37], while quercetin at concentrations of 16 µg/mL produced the highest inhibitory antibiofilm formation effect against PA01 among the concentrations used -8, 16, 32 and 64 µg/mL [19].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Figure 2 ii-b) [7,56]. Overall, our findings concur with previous studies that have documented that these phytochemicals can inhibit biofilm formation [19,37]. For instance, baicalein has been reported to inhibit P. aeruginosa PA01 biofilm formation at concentrations of 32-128 µg/mL [37], while quercetin at concentrations of 16 µg/mL produced the highest inhibitory antibiofilm formation effect against PA01 among the concentrations used -8, 16, 32 and 64 µg/mL [19].…”
Section: Discussionsupporting
confidence: 90%
“…In fact, at higher concentration it was observed that both free flavonoids seem to be toxic towards the E. coli Top 10 biosensor. Both phytochemicals had been reported to inhibit quorum sensing-dependent processes in a P. aeruginosa PA01 strain, but this is only achieved at higher concentrations too [19,37]. However, in their encapsulated forms, our results demonstrate that their QS inhibition ability improves when tested in our E. coli Top 10 biosensor.…”
Section: Discussionmentioning
confidence: 63%
“…Molecules with QS inhibitory activity are of special interest against P. aeruginosa due to the burgeoning antibiotic resistance and unfavourable outcomes of inflammatory injury after the infection (Luo et al . ).…”
Section: Resultsmentioning
confidence: 97%
“…3d). Biofilm has clinical significance as it plays a key role in the ability of organisms to resist antibiotics and persist in long-term infections such as cystic fibrosis and indwelling medical devices (Singh et al 2000;Donlan 2001;Popat et al 2012 special interest against P. aeruginosa due to the burgeoning antibiotic resistance and unfavourable outcomes of inflammatory injury after the infection (Luo et al 2016).…”
Section: Resultsmentioning
confidence: 99%
“…This current study adds to the research on the anti- Borrelia activity of Scutellaria baicalensis . This botanical and/or baicalein have also been shown to have antimicrobial activity (133, 134), synergistic effects with antibiotics (135139) and reduce biofilm formation in Pseudomonas aeruginosa models (140, 141).…”
Section: Discussionmentioning
confidence: 99%